A Novel Lateral Flow Assay for Rapid and Sensitive Nucleic Acid Detection of Avibacterium paragallinarum - Huo, Caiyun; Li, Donghai; Hu, Zhenguo; Li, Guiping; Hu, Yanxin; Sun, Huiling (Frontiers in Veterinary Science, 2021)
Avibacterium paragallinarum, the pathogen of infectious coryza, caused a highly contagious respiratory disease that poses a serious threat to chickens. Hence, it is necessary to do diagnostic screening for Av. paragallinarum. Existing technologies have been used for Av. paragallinarum testing, which however have some drawbacks such as time-consuming and expensive that require well-trained personnel and sophisticated infrastructure, especially are limitedly feasible in some places lack of resources. Nucleic acid hybridization-based lateral flow assay (LFA) is capable of dealing with these drawbacks which attributes to the advantages of low-cost, rapid and simple. However, nucleic acid determination of Av. paragallinarum through LFA method has not been reported so far. In this study, we developed a novel LFA method that employed gold nanoparticle probes to detect amplified Av. paragallinarum dsDNA. Compared with agarose gel electrophoresis, this LFA strip was inexpensive, simple-to-use and time-saving, which displayed the visual results within 5-8 min. This LFA strip had higher sensitivity that achieved the detection limit of 101 CFU/mL as compared to 102 CFU/mL in agarose gel electrophoresis. Besides, great sensitivity was also shown in LFA strip and no cross reaction existed for other bacteria. Furthermore, Av. paragallinarum in clinical chickens with infectious coryza were perfectly detected by our established LFA strip. Our study is the first to develop the LFA integrated with amplification and sample preparation techniques for better nucleic acid detection of Av. paragallinarum, which holds great potential for rapid, accurate and on-site determination methods for early diagnosis of Av. paragallinarum to control further spreading.